Prevalence of Oral Habits (Finger Sucking) Among Preschool Children in Zliten, Libya - Amal Aljedaemi; Hwas, Rema; Salimah Himeer; Alkhansa Ghabasa (AlQalam Journal of Medical and Applied Sciences, 2025)
Non-nutritive sucking habits (NNSH), particularly finger sucking, are common repetitive behaviors in childhood. While often self-limiting, prolonged habits can lead to significant dentoalveolar malocclusions, such as anterior open bite and posterior crossbite. The severity of these complications depends on the frequency, intensity, and duration of the habit. This study aimed to determine the prevalence of finger-sucking habits among preschool children in Zliten, Libya, and to assess the relationship between the habit and demographic factors such as age and gender. A cross-sectional study was conducted involving 1,025 children (507 boys and 518 girls) aged 3 to 6 years enrolled in public kindergartens in Zliten city during the 2022–2023 academic year. Data were collected using questionnaires distributed to mothers, obtaining information on demographics and specific sucking behaviors. Data were analyzed using SPSS (version 21), utilizing the Chi-square test to determine statistical significance (P<0.05). The overall prevalence of finger sucking in the study population was 11.4%. Among those with the habit, the thumb was the most frequently involved digit (67.5%). No statistically significant association was found between gender and finger sucking (P>0.05). However, a statistically significant relationship was observed regarding age (P<0.001), with the prevalence of the habit decreasing as children grew older (50% in 3-year-olds vs. 7.4% in 6-year-olds). The prevalence of finger sucking in Zliten is lower than that reported in several international studies, but it remains a clinical concern for the minority of children who persist in the habit. Early detection and parental education regarding the potential risks of malocclusion are essential to encourage cessation of the habit before the eruption of permanent dentition.